2011
DOI: 10.2169/internalmedicine.50.4361
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Mucosal Damage Evaluated by Transnasal Endoscopy and QOL Assessments in Ischemic Heart Disease Patients Receiving Low-dose Aspirin

Abstract: Objective Transnasal endoscopy was conducted to examine gastric mucosal damage in Japanese patients with ischemic heart disease who were receiving low-dose aspirin for preventing the onset or recurrence of cardiovascular disease. Patients and Methods An endoscopist assessed gastric mucosal damage. Furthermore, the MOS 36-Item Short-Form Health Survey (SF-36 ) and the Gastrointestinal Symptom-Rating Scale (GSRS) were used to assess the outcomes of their quality of life (QOL) and the possible presence of gastric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 10 publications
0
5
1
Order By: Relevance
“…However, in our study, no significant differences were found between patients with gastric ulcer or those who did not take aspirin [50,51]. Among patients with DI, LDA users had significantly lower MCS than nonusers.…”
Section: Discussioncontrasting
confidence: 75%
“…However, in our study, no significant differences were found between patients with gastric ulcer or those who did not take aspirin [50,51]. Among patients with DI, LDA users had significantly lower MCS than nonusers.…”
Section: Discussioncontrasting
confidence: 75%
“…It is known that patients with peptic ulcer have lower QOL than healthy people and that patients taking aspirin experience decreased QOL. However, in our study, no significant differences were found between patients with gastric ulcer or those who did not take aspirin [ 50 , 51 ]. Among patients with DI, LDA users had significantly lower MCS than nonusers.…”
Section: Discussionmentioning
confidence: 66%
“…Other studies did not detect such an association, reporting that the presence or absence of H. pylori infection was not associated with the incidence of gastric ulcer in NSAIDs users [14]. Other studies did not detect such an association, reporting that the presence or absence of H. pylori infection was not associated with the incidence of gastric ulcer in NSAIDs users [14].…”
Section: Discussionmentioning
confidence: 99%